import proveit
from proveit import defaults
from proveit import A, B
from proveit.logic import TRUE, Not, Equals, NotEquals, in_bool
theory = proveit.Theory() # the theorem's theory
%proving untrue_antecedent_implication
defaults.assumptions = (A, NotEquals(A, TRUE))
contradiction = NotEquals(A, TRUE).derive_contradiction()
not_b_contradiction = contradiction.as_implication(Not(Equals(B, TRUE)))
BeqT_via_contradiction = not_b_contradiction.derive_via_contradiction()
B_via_contradiction = B.prove()
B_via_contradiction.as_implication(A)
%qed